Evaluation of integrin αvβ6 cystine knot PET tracers to detect cancer and idiopathic pulmonary fibrosis - Richard H. Kimura (Nature Portfolio, 2019)
Knottin is a cystine knot peptide. Here, the authors develop a knottin-based tracer for positron emission tomography and demonstrate its ability to detect cancer and idiopathic pulmonary fibrosis through selective binding to integrin αvβ6.